The Effectiveness of Fingerhold Relaxation Techniques and Lemon Aromatherapy Towards Reducing Pain Intensity in Post Section Caesarian Patients - Fenty Ika Wardani; Elfira Sri Futriani (STIKep PPNI Jawa Barat, 2022)
Aims : A person who experiences pain will have an impact on daily activities such as meeting the need for sleep, rest, and individual fulfillment as well as aspects of social interaction and, if not treated, can lead to neurogenic shock. Pain management can be done with several actions or procedures, both pharmacologically and non-pharmacologically. One of the non-pharmacological pain management techniques is the finger grip relaxation technique. This study aimed to Giving birth by Sectio Caesarea generally experiences pain due to surgical wound surgery. Design : The research design used quasy experimental with pre test-post test control group. Methods : This study conducted in November 2021. The sample in this study were all patients post Sectio Caesarea. The study samples as many as 100 people. Sampling using accidental sampling technique. Results : In the intervention group and the control group before being treated, most of them experienced moderate pain, and after being treated, most of the intervention group had mild pain, while in the control group they had moderate pain and some even experienced severe pain Conclusions : There was a difference in the average decrease in pain intensity in post-Section Caesarea patients who were given finger grip relaxation and lemon aromatherapy in the pre-intervention and post-intervention measurements in the intervention group and the control group.